Residential child care practitioners in autism-specific units: the perceptions of potential staff and newly recruited current practitioners - Irene Stevens (Scottish Journal of Residential Child Care)
This paper presents findings about the beliefs and experiences of potential and current residential child care practitioners who work with children affected by autism spectrum disorders (ASD). Some children and young people affected by ASD live in residential care. This can be a residential school’s short break service or long-term home. Residential child care practitioners are those who provide direct care, 24 hours a day, for the young people who live in these facilities. In Scotland, such practitioners are required to be registered for practice and provide a vital service to this group of young people.